Pengaruh Produk dan Promosi terhadap Keputusan Pembelian Air Minum Merek Club di Kelurahan 3-4 Ulu kota Palembang - Pratiwi, Juriyah; Asiati, Diah Isnaini; Fitantina (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
The The purpose of this research is to determine the influence of products and promotions on decisions to purchase club brand drinking water in the community of Subdistrict 3-4 Ulu Palembang simultaneously and partially. This research includes associative research. The research population is infinite, with a sample size of 100 respondents. The data used is primary data. The sampling technique is Probability Sampling using the Purposive Sampling method. The data collection technique in research is by questionnaire. The data analysis used in this research is Multiple Linear Regression analysis. The results of Multiple Linear Regression show that there is a positive influence of Product and Promotion variables on the Decision to Purchase Club Brand Drinking Water in Subdistrict 3-4 Ulu Palembang. The results of the F hypothesis test show 1) There is a significant influence of Product and Promotion variables on the Decision to Purchase Club Brand Drinking Water in Subdistrict 3-4 Ulu Palembang. The results of the t hypothesis test show 2) There is a significant influence of the Product variable on the Decision to Purchase Club Brand Drinking Water in Subdistrict 3-4 Ulu Palembang. 3) There is a significant influence of the Promotion variable on the decision to purchase Club Brand Drinking Water in Subdistrict 3-4 Ulu Palembang. The results of the coefficient of determination show that the Adjusted R Square value means that purchasing decisions can be explained